Field study on attached cultivation of Arthrospira (Spirulina) with carbon dioxide as carbon source. (July 2019) - Wang, Junfeng; Cheng, Wentao; Liu, Wen; Wang, Hui; Zhang, Dongcun; Qiao, Zhanshan; Jin, Guiyong; Liu, Tianzhong
Highlights: Field performance of attached cultivation for microalga was investigated. Biomass yield of 38.3 g m −2 d -1 with CO2 usage efficiency of 75.1% were achieved. Construction costs for building the system were also analyzed. Attached cultivation was promising technology for application of microalga in CCUS. Abstract: Microalga is considered as a promising candidate for CO2 bio-sequestration. Biofilm attached cultivation is a newly developed technology with many advantages over conventional aqua-suspended methods. In this research, the field performance of this technology was investigated with a 10 m 2 pilot system under greenhouse condition by cultivating Arthrospira (Spirulina) platensis with CO2 as carbon source. The system run continuously for two months without contamination bloom. Averaged biomass productivity was 38.3 g m −2 d -1 with protein content over 60% and overall CO2 usage efficiency of 75.1%. Construction cost for the pilot system was over US200 per m 2 which was much higher than that of open pond. However, there was a great reduction space in future large-scale application if the most expensive materials were substituted with cheaper ones. These results indicated the attached cultivation was a promising technology for industrialized application of microalga in CCUS (carbon capture, utilization and storage).